Postoperative Arrhythmia Repair of Tetralogy of Fallot in Pediatrics - Santoso, Febrina Mustika; Prishanti, Nadira; Rahma, Naswa Arvieda; Abdullah, Mokhammad Faisol; Kusumaningrat, Dorothea Respa (International Journal of Public Health Excellence (IJPHE), 2023)
Tetralogy of Fallot (ToF) is the most common cyanotic congenital heart disease. ToF affects 3% to 10% of all babies born with congenital heart disease. Arrhythmia is a common complication following congenital heart surgery. As a medical guide, it is important to know Arrhythmia as a complication after ToF surgery. Method : The author searched, selected, and chose journals related to Arrhythmia after ToF repair surgery through several research databases including ScienceDirect, Google Scholar, PubMed, and Wiley. by using the keywords "Arrhythmia", "Surgery", "Pediatrics" and "Tetralogy of Fallot". The results of the literature search were 2,006 journals with 21 journals meeting the selection criteria, and 6 studies that would be analyzed further. Results and Discussion : Arrhythmia after heart surgery is a common complication that occurs. The most common type of arrhythmia that occurs after ToF repair surgery is JET. This arrhythmia is associated with injury to the heart's conduction system during surgery. JET is a life-threatening tachyarrhythmia that occurs especially after procedures near the AV node (AVN), such as ToF repair operation. The main risk factor for postoperative arrhythmias is a longer cardiopulmonary bypass time. Conclusion : Arrhythmia is a common complication that occurs after ToF repair surgery and is an important cause of morbidity and mortality if not treated immediately.